Effect of ion irradiation of the metal matrix on the oxidation rate of Zircaloy-4. (15th May 2018) - Tupin, Marc; Verlet, Romain; Colas, Kimberly; Jublot, Michael; Baldacchino, Gérard; Wolski, Krzysztof
Highlights: Proton irradiation at 350 °C produces < a > -dislocation-loops in the alloy which increases the oxidation rate. Zr ion irradiation at 20 °C induces mainly an amorphization of the Zr(Fe, Cr)2 precipitates which does not affect the oxidation rate of Zy4. Iron irradiation (implantation+ damage) of the matrix does not seem to play a strong kinetic role on the corrosion of Zy4. Abstract: The oxidation kinetics acceleration observed in Zircaloy-4 cladding in Pressurized Water Reactor could be partially due to metal irradiation damage occuring in-pile. To check this assumption, several ion irradiation tests of the Zircaloy-4 metal matrix were performed to reproduce the evolution of the metallurgical state in reactor. This study showed that the amorphization process of the intermetallic precipitates (SPPs) does not change significantly the oxidation rate of Zircaloy-4. Implantation of iron in the matrix to simulate iron dissolution from the SPPs has no real impact on the corrosion kinetics. However proton irradiations at 350 °C producing dislocation loops resulted in a significant increase in the oxidation rate.